THE IMPACT OF SANITATION ON GROUNDWATER NITRATE LEVEL IN BANTUL DISTRICT, BANTUL REGENCY, YOGYAKARTA SPECIAL PROVINCE, INDONESIA - Salpisey Heng; Doni Prakasa Eka Putra; Wahyu Wilopo (Journal of Applied Geology, 2015)
Bantul is one district of Yogyakarta Special Province which residents mostly use on-site sanitation. On-site sanitation is well-known for hot-spot system of nitrate groundwater contamination. It is because the wide-practice of failure of on-site sanitation systems. Besides, the failure of on-site sanitation system, it will depend on the age of settlement, population density, sanitation arrangement and sanitation behavior including water use patterns. Because of this, nitrate has leaked to groundwater and polluted many supply wells surrounding the septic systems. Since the repeated intake of nitrate could cause various acute and chronic effects to human health, especially the infant’s health under 3 months (blue baby syndrome), it is crucial to undertake the study of impact of sanitation on groundwater nitrate level in Bantul district to acquire a better understanding of the effect of settlement age, population density, sanitation arrangement and sanitation behavior on the concentration of nitrate in groundwater. In order to recognize or achieve the understanding of this issue, a methodology is conducted by observation directly to the field, including the measuring of groundwater table and the distance of septic tank to well, and also make the questionnaires for the mentioned parameters. Finally, the result of each factors (Sanitation arrangement, Settlement age, House density) are shown a low relationship with nitrate concentration, although water use patterns does not. However, the combination of these three factors can show up to find out a better correlation than one factor with this nitrate concentration. Although it has a good relationship with nitrate concentration (average), the variation of nitrate concentration from high to low shows a low relationship. Therefore, the importance of groundwater vulnerability cannot be overlooked in explaining the variation in contaminant concentrations because the nitrate concentration in the groundwater does not only depend on contaminant loading but also groundwater vulnerability. Keywords: Groundwater, on-site sanitation, nitrate concentration, contaminant loading